Antecedents to Consumer Peer Communication through Social Advertising: A Self-Disclosure Theory Perspective. Issue 1 (2nd January 2018) - Ardiansyah, Yusfi; Harrigan, Paul; Soutar, Geoffrey N.; Daly, Timothy M.
ABSTRACT: The use of peer communication has become a primary method used by advertisers to disseminate their messages to relevant consumers on social media—with a significant return on investment. This study examines whether consumers' privacy, trust, and perceived benefits are associated with their peer communication through social advertising within the lens of self-disclosure theory. The results of a survey of 393 social network users in Indonesia demonstrate that trust is a key factor promoting peer communication through social advertising, mediating privacy concerns and perceived privacy control. Of the three types of peer-communication benefits examined, social benefits appear to be the most significant antecedent, ahead of economic benefits and entertainment benefits. These findings have theoretical and managerial implications.